2006
DOI: 10.1128/jb.01278-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of RelGsuin Stress Response and Fe(III) Reduction inGeobacter sulfurreducens

Abstract: Geobacter species are key members of the microbial community in many subsurface environments in which dissimilatory metal reduction is an important process. The genome of Geobacter sulfurreducens contains a gene designated rel Gsu , which encodes a RelA homolog predicted to catalyze both the synthesis and the degradation of guanosine 3,5-bispyrophosphate (ppGpp), a regulatory molecule that signals slow growth in response to nutrient limitation in bacteria. To evaluate the physiological role of Rel Gsu in G. su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…9 Evidence for the involvement of CcpA in oxidative stress response was obtained previously from a mutant in rel GSU , a gene encoding a homolog of the stress response protein RelA/SpoT. 32 Here, various genes linked to oxidative stress were down-regulated and the rel GSU mutant also showed increased susceptibility to oxidative stress compared to the wild type. 32 GSU2813 was among the regulated genes and it does seem to form part of a complex answer of the bacterium to the presence of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 91%
“…9 Evidence for the involvement of CcpA in oxidative stress response was obtained previously from a mutant in rel GSU , a gene encoding a homolog of the stress response protein RelA/SpoT. 32 Here, various genes linked to oxidative stress were down-regulated and the rel GSU mutant also showed increased susceptibility to oxidative stress compared to the wild type. 32 GSU2813 was among the regulated genes and it does seem to form part of a complex answer of the bacterium to the presence of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 91%
“…An earlier study from our group (Leang and Lovley, 2005) also demonstrated that functional σ 70 family promoter elements within four protein-coding genes, GSU2735 (orfS), GSU2741 (orfR), GSU2732, and GSU2738 (orf2), regulate the expression of the omcB and the omcC operons of G. sulfurreducens. These genes are transcribed and translated, as demonstrated by multiple expression and proteomic experiments (Núñez et al, 2004;Leang and Lovley, 2005;DiDonato et al, 2006;Ding et al, 2006;Kim et al, 2008;Nevin et al, 2009). This suggests that the predicted PilR binding sites located within ORFs are of functional significance rather than false positive results.…”
Section: Patternmentioning
confidence: 89%
“…Although the SR is a central stress response, only a few studies have examined its role in oxidative stress. For example, the relA mutant of Enterococcus faecalis is more susceptible to H 2 O 2 challenge than the wild type (14,15), while aerobic growth of the relA mutant of Geobacter sulfurreducens is impaired due to oxidative stress (56). Additionally, we and others have recently shown that SR inactivation in P. aeruginosa led to increased oxidant susceptibility (33,57).…”
Section: Discussionmentioning
confidence: 99%